Lithobius (Ezembius) hualongensis sp. nov. and Lithobius (Ezembius) sui sp. nov. (Lithobiomorpha, Lithobiidae), two new species of centipede from northwest China - Penghai Qiao; Wen Qin; Huiqin Ma; Gonghua Lin; Tongzuo Zhang (ZooKeys, 2019)
Lithobius (Ezembius) hualongensis sp. nov. and Lithobius (Ezembius) sui sp. nov. (Lithobiomorpha, Lithobiidae) recently discovered from the Qinghai-Tibet Plateau, China are described. Morphologically, the two new species are very similar but can be distinguished by the number of coxosternal teeth: L. (E.) hualongensis sp. nov. has 2 + 2 while L. (E.) sui sp. nov. has 3 + 3. The two new species resemble L. (E.) multispinipes Pei et al., 2016, from the Xinjiang Autonomous Region, but can be readily distinguished by having the Tömösváry’s organ slightly larger than the adjoining ocelli rather than smaller, 3 + 3 spurs on female gonopods versus 2 + 2, and the simple terminal claw of female gonopods with a small triangular protuberance on the basal ventral side versus simple, without a small triangular protuberance on the basal ventral side. We also compare the main morphological characters of the two new species with the other Lithobius (Ezembius) species known in Qinghai Province. A key to the Chinese species of Ezembius is presented.